2009
DOI: 10.1111/j.1751-1097.2009.00552.x
|View full text |Cite
|
Sign up to set email alerts
|

The Vitamin D Status Among Tibetans

Abstract: UVB from the sun and intake from food are the only human sources of vitamin D. Tibet is a unique region for comparisons of these sources: (1) it lies at a low latitude and at a high altitude and has very large annual fluences of UVB; (2) the traditional Tibetan food is poor in vitamin D. Blood samples were taken from 63 persons of different age, with different occupations and staying at different places. UVB doses at these places were measured. The samples were analyzed by a standard radioimmune assay for dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…In agreement with our previous article [19], there is a great difference in levels We have tested the 25(OH)D level in different gender. The data of Figure 6 (the average group is the mean value of the Lhasa, Shigatse, Tingri, Nagqu)…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…In agreement with our previous article [19], there is a great difference in levels We have tested the 25(OH)D level in different gender. The data of Figure 6 (the average group is the mean value of the Lhasa, Shigatse, Tingri, Nagqu)…”
Section: Resultssupporting
confidence: 62%
“…A standard radioimmune assay was employed to determine the serum concentrations of 25(OH)D [19]. Nagqu (11.5 ± 4.9 ng/mL), Shigatse (11.9 ± 4.7 ng/mL) and Tingri (13.4 ± 6.5 ng/mL) during 2012 and 2013.…”
Section: Methodsmentioning
confidence: 99%
“…Most human studies have observed an important correlation between sun exposure and vitamin D levels accounting for more than 50% of changes in vitamin D status (25,45). Ultraviolet B light exposure is increased at higher altitude; however, several studies have shown significant vitamin D deficiency in humans, including pregnant women, living in high-altitude locations (2,34,37). In addition to vitamin D deficiency, high-altitude residents are exposed to hypobaric hypoxia, a major risk factor for pregnancy complications.…”
mentioning
confidence: 99%
“…Research covering topics from its effectiveness to its ability to integrate with western medicine has begun to develop both in Tibetan regions and the west [12][13][14][15][16][17][18][19][20]. This research is a good start but to often lacks more rigorous scientific investigations.…”
Section: Future Developmentsmentioning
confidence: 99%